A Comparative Study of Weekend Developmental Curriculum in Davao City Philippines - Deporos, Saprolla Rollie; , Agus Wijayanto, Ph.D; , Dr. Anam Sutopo, M.Hum (Universitas Muhammadiyah Surakarta, 2015)
Education is a lifelong process. It begins the day we are born and ends the day we die. Found in every society, it comes in many forms it could be formal education, informal education or learning by experience. It is a collection of information that makes an individual, being a human as human that holds and secures the future of young generations. The Weekend Madrasah is basically a system of education to save the Muslim Filipino communities and preserve their traditions and cultures from the malady of Western education. Hence the objectives of this study are (1.) to find out the reasons of disunity of curriculum or being ununified curriculum (2.) to look for a remedy of the situation (3.)To recommend ALIVE program as an answer of the existing circumstances of the Madrasah Comprehensive Program. The research is interesting due its characteristics such as the Madrasah Comprehensive Development and Promotion program is the axis of traditional developmental Islamic basic education implementation in each Muslim society every Saturday and Sunday in Davao City that holds frequent learners and the Arabic Language and Islamic Values Education or ALIVE program under the Department of Education holds the Muslim populated public schools nationwide to be implemented the basic Islamic education. Concerning the quality of Islamic basic education this thesis will give information the difference of the two major Islamic education programs systemize and organize it's effectively implementation. Data collected through qualitative approach which consisted by analyzing the written documents available, interviews with the school heads, teachers involved, casual conversation with students and alumni, formal discussion was made and an individual analization in order to accumulate the sequence of information. Consequently the study found out the following (1.) The implementation of Madrasah Comprehensive and Promotion Program in Davao city is stationary in a sense of developing their system and progress of their implementation (2.) Each Madrasah under weekend developmental program have their own curriculum used (3.) the malady of the situation triggered the declination instead of growth. This study opens a chance to understand the needs of Muslim educators about the characteristics of curriculum to be an effective institution.